Jacobson, David. 1991. Reading Ethnography. United State : State University of New York Press, 158 pages. ISBN : 978-0791405475 - Efriani Efriani (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2023)
David Jacobson is an American anthropologist and Professor Emeritus in the Department of Anthropology at Brandeis University. Reading Ethnography was published by the State University of New York Press in 1991. Reading Ethnography provides a model for analyzing and evaluating ethnographic arguments. Through this book, David Jacobson examines the relationship between anthropologists' claims about human behavior and the data they use to support the claims they build. Jacobson analyzes the textual organization of ethnography, focusing on how problems, interpretations, and data are brought together. He examines in detail several well-known ethnographic cases, which he selected to illustrate the basic theoretical framework and mode of analysis. By advancing a method for assessing ethnographic exposure, this book contributes to the role of rhetoric and reflexivity in anthropology.